Pre-Service Teacher's Intellectual Virtues Andonline Information Literacy - Meekaew, Nattapon (Տիգրան Մեծ)
Intellectual virtues and online information literacy are critical issues in education. This has a significant impact on the development of pre-service teachers‟ learning skills, as they will play an important role in transferring knowledge to students in the future. This article investigates the relationship between intellec-tual virtues and information literacy among pre-service teachers on an online platform. To collect qualita-tive data, in-depth interviews and focus group discussions were used. Thirty pre-service teachers from three universities in northeastern Thailand served as key informants. The philosophical analysis was used to analyze the data, along with phenomenological analysis. The results looked into the intellectual virtues that pre-service teachers needed to improve their learning skills. Curiosity played a role in encouraging pre-service teachers to improve theircritical thinking skills when dealing with online information. Fur-thermore, intellectual thoroughness and intellectual attentiveness were helpful for pre-service teachers to improve information literacy skills. Improving pre-service teachers‟ information literacy through various instructional approaches was beneficial in allowing them to make rational choices when accessing online information. The article suggests higher education institutes providing more instructional practices to pre-service teachers toboost their critical thinking skills and information literacy on an online platform
Keywords: Philosophy of education